Emerging Roles of GluN3B NMDA Receptor Subunit in the Central Nervous System - Yuerou Huang; Junyi Xie; Jiamin Chen; Siman Guo; Yuan Li; Fang Liu (Neuroscience Bulletin, 2026)
GluN3B is the most recently identified subunit of N-methyl-d-aspartate receptors (NMDARs), and gradually it has been found that it may be involved in regulating the development of central nervous system (CNS)-related diseases. Compared with the traditional NMDARs containing only GluN1 and GluN2 subunits, non-classical NMDARs with GluN3 have non-conventional biophysical, trafficking, and signaling properties. As a negative regulatory subunit that diminishes or inhibits classical NMDARs' functions, GluN3B plays important roles in synaptic plasticity and neuronal survival, and may be associated with CNS disorders such as schizophrenia and substance use disorders. However, the number and depth of studies on how GluN3B is involved in the regulation of related diseases are very limited. This review summarizes the expression and physiological characterization of GluN3B-NMDARs and provides an overview of their emerging roles in psychiatric and neuropsychiatric disorders, aiming to provide a basis for understanding disease mechanisms and developing novel therapeutic targets.